Inhabiting la patria : identity, agency, and antojo in the work of Julia Alvarez - Harrison, Rebecca L., 1970-; Hipchen, Emily, 1964- (Albany : State University of New York Press, 2013)
"Provides insightful criticism from many perspectives and grants in-depth analyses of both well-known and lesser studied texts"--Provided by publisher
Introduction: Inhabiting La Patria: Identity, Agency, and Antojo in the Work of Julia Alvarez -- Chapter 1. Julia Alvarez and the Autobiographical Antojo -- Chapter 2. Yo! on the Margins : Dividing the Family and the Ethnic Writer as Traitor -- Alvarez's Critique of the Dominican Family -- The Ethnic Writer as Traitor -- Conclusion: They're Not Characters, They're My Family -- Chapter 3. Super-Size Me : Ritual as Affluenza in Julia Alvarez's Once upon a Quinceatera : Coming of Age in the USA -- Chapter 4. Rewriting Master Narratives : Julia Alvarez's In the Time of the Butterflies -- Chapter 5. Patriots and Citizens of the Planet : Friendship and Geopolitics in Julia Alvarez's Young Adult Fiction -- No Flies Fly into a Closed Mouth: Friendship, Testimonio, and Freedom -- Adopting a Transnational Sense of Self: Living Youth Activism outside the Box -- Patriots and Citizens of the Planet: Transcending Borders in Return to Sender and the Ta Lola Novels -- Concluding Thoughts: Teaching and Learning from Julia Alvarez's Young Adult Fiction -- Chapter 6. Isolation on Hybridity Road: Complexities of Identity Formation in Julia Alvarez's Something to Declare -- Chapter 7. Between the Scylla and the Charybdis: Remapping Subjectivity in the Dialogic Waters of Julia Alvarez's The Other Side/El Otro Lado -- Chapter 8. In the Name of Saloma : Julia Alvarez's Feminist Discourse on La Patria -- Chapter 9. The Hidden Archivis t; Or, Julia Alvarez's Historical Fiction beyond the Borders -- In-Between and Beyond : Alvarez's Historical Narrator -- Other Archives: Collective Oral History and Narrative Identity -- Saving Salome and Writing the Self -- Saving the Wor(l)d -- Conclusion --Contributors -- Index
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Alvarez, Julia -- Criticism and interpretation; Alvarez, Julia; Dominican literature -- History and criticism; Littérature dominicaine -- Histoire et critique; LITERARY CRITICISM -- American -- General; Criticism, interpretation, etc